Hubungan Self Efficacy dan Self Directed Learning Readiness (SDLR) Terhadap Kemampuan Keterampilan Klinis Mahasiswa S1 Kedokteran - Daffa Pratama Wijaya; Romadhoni Romadhoni; Mega Pandu Arfiyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Clinical skills are essential competencies that serve as foundational provisions in medical education, particularly in shaping students’ readiness for professional practice. Two important psychological and behavioral attributes that influence the development of clinical skills are self-efficacy and self-directed learning readiness (SDLR). Self-efficacy refers to an individual's belief in their own ability to execute behaviors necessary to produce specific performance attainments, emphasizing the role of self-confidence in clinical tasks. Meanwhile, SDLR reflects a student's willingness and preparedness to take responsibility for their own learning, which is critical in the context of self-regulated and lifelong learning in medical education. This study aimed to analyze the relationship between self-efficacy and SDLR on the clinical skill competencies of first-year medical students at the Faculty of Medicine, Muhammadiyah University Semarang (UNIMUS). A quantitative, observational analytic study was conducted using a cross-sectional approach. The instruments used were the General Self-Efficacy Scale (GSES) and Self-Directed Learning Readiness Scale (SDLRS). The study involved 120 first-year medical students, selected through total sampling. Data were analyzed using the Spearman correlation test. The results indicated a significant positive relationship between self-efficacy and clinical skills (p = 0.005; r = 0.254), and between SDLR and clinical skills (p = 0.009; r = 0.238). Although the correlation strength was weak, the direction was positive, suggesting that higher levels of self-efficacy and SDLR are associated with better clinical skills performance. These findings highlight the importance of fostering psychological readiness and self-directed learning habits among medical students to support the development of essential clinical competencies.